The Effect of Tax Aggressiveness on Company Value with Green Accounting as a Moderating Variable - Wardani, Dewi Kusuma; Abinowo, Agaphe Christian; Cholifiana, Fina (Journal of Management and Business Review, 2025)
This study examines, using green accounting as a moderator, how tax aggressiveness affects a company's worth. On the BEI for 2013 - 2022, researchers used mining companies. Purposive sampling yielded 23 companies, or 100 observations, based on the approach. The moderated regression analysis method was applied to analyze the data. This study indicates that tax aggressiveness increases firm value and that the relationship between tax aggressiveness and company value is positively correlated with green accounting. It can be concluded that tax aggressiveness has a positive effect on company value, and green accounting strengthens the relationship between tax aggressiveness and company value. The implication is that tax aggressiveness can reduce a company's reputation and impact its company value. Research is limited to tax aggressiveness, company value, and green accounting as moderating variables. Future researchers are advised to conduct further research using a large sample of companies, adding research periods, and using the most recent period.